Emergence of Hybrid CSR Models as a Conflict‐Driven Communicative Process in a Nordic Welfare State - Moisander, Johanna; Eräranta, Kirsi; Fahy, Kathryn M.; Penttilä, Visa (Journal of Management Studies, 2024)
AbstractThis paper offers an understanding of how hybrid models of corporate social responsibility (CSR) – models combining society‐centric mandatory (implicit) and business‐centric voluntary (explicit) approaches to CSR – are communicatively constructed through institutional struggles over the roles and responsibilities of business in society, in the context of a Nordic welfare state. We develop a model of hybridization as a dialectical process of communicative activity, framing and counter‐framing, in which conflict and contestation over normative understandings about CSR drive the process. The model explains the emergence of hybrid models of CSR in terms of gradually evolving issue development and frame changes that are driven by discursive struggles over moral obligations of business in society, appropriate configuration of legitimacy relationships, and appropriate institutional arrangements for CSR governance. In contrast to prevailing accounts, which tend to theorize hybridization as resulting from isomorphic, mimetic, and normative pressures, our account explicitly attends to the politics of hybridization.